The ICT Management in Education in the Era of Digital Disruption: Analysis of the Challenges of Digital Divide, Teacher Competence, and Data Security as Urgent Issues in Indonesian Education - Rompas, Parabelem Tinno Dolf; Sumampow, Zoya Febrina; Mongkau, Waraney Josua; Wohon, Oktafio Fabio; Laia, Yosua Swardin; Lase, Karnius (International Journal of Information Technology and Education, 2025)
The development of information and communication technology (ICT) has brought significant changes to the education system, especially following the era of digital disruption and the widespread adoption of online learning during the pandemic. In the context of Indonesian education, the use of ICT not only creates new opportunities for improving the quality of learning but also introduces various challenges that require strategic management. This scientific article analyzes ICT management in education by highlighting three pressing issues: the digital divide between regions, the low level of teachers’ digital competence, and the increasing threats to educational data security. This study employs a literature review method to collect and analyze references related to ICT management, digital learning theories, government policies, and technology integration models such as TPACK and SAMR. The analysis shows that the implementation of ICT in schools remains uneven due to limited infrastructure, insufficient teacher training, and weak data protection systems. Furthermore, the findings indicate that well-planned, organized, and sustainable ICT management is essential for building an educational ecosystem that is responsive to technological advancements. The article concludes that ICT can only have a significant impact when supported by strategic planning, strong digital security policies, improved human resource competence, and enhanced government support. Therefore, ICT management serves as a crucial foundation for realizing an inclusive, secure, and sustainable digital education system in Indonesia.